Calcium channel blocker and risk of postoperation lymphatic-related complications among gynecologic malignances - Jiang, Haote; Sun, Mengxiao; Shao, Rongrong; Su, Shuyue; Zhang, Yuyang (Frontiers in Surgery, 2023)
Purpose: This study was performed to assess the association of calcium channel blocker (CCB) and other potential factors with postoperative lymphatic-related morbidity in patients with cervical cancer and endometrial carcinoma. Methods: Patients diagnosed with cervical cancer or endometrial carcinoma with pelvic lymphadenectomy between January 2017 and January 2022 were enrolled. Postoperative lymphatic-related morbidity was evaluated by calculating the lymph cyst occurrence within 3 months after surgery and the duration of pelvic drainage. Univariate analyses evaluating the risk factors for lymphatic-related morbidity were performed. Results: Of a total of 251 patients, 52 patients were diagnosed as lymphatic cysts by B-ultrasound or computed tomography, and the duration of drainage from 110 patients exceeded the average number of days. The use of calcium channel blocker is a factor affecting the post-operation recovery. Univariable analysis revealed that hypertension, CCB and lymph node metastasis were independent predictors of postoperative complications. Conclusions: This study demonstrated that CCB may be a factor which associated with incidence of post-operation lymph cyst, and CCB usage prolongs the duration of pelvic drainage.